Visualization of forest fires interactively on the internet - Gumusay, Mustafa Umit; Sahin, Kemal (ACADEMIC JOURNALS, 2009)
The Internet has rapidly changed the transfer and dissemination of geographical information. The rapid and enormous development of the Internet technology has resulted in usage of the Internet as a tool for data access, data transmission and access to GIS analysis tools. The combination of Geographic Information System (GIS) and the Internet offers great possibilities, such as interactive access to geospatial data, enhancement of the functions of geographic information and the access of to GIS analysis tools. The Internet GIS is a GIS tool that uses the Internet for displaying spatial data and analysis results. It is necessary to make use of GIS and Internet technologies in order to struggle with wildfires, which are causing great amount of loss every year and to contribute to planning activities. By means of these technologies, it is possible to gather necessary spatial data from different resources and to prepare products, which will contribute to the decisions of fire managers. In this study, usage of GIS in the phases of wildfire management was researched. The aim of the study is to establish wildfire information management system in order to help wildfire managers to reduce fire risk and make use of resources effectively and economically.
Keywords: GIS; the internet; ASP; AspMap; Science & Technology - Other Topics